2021
DOI: 10.1089/omi.2021.0025
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell Marker CD44 Plays Multiple Key Roles in Human Cancers: Immune Suppression/Evasion, Drug Resistance, Epithelial–Mesenchymal Transition, and Metastasis

Abstract: One of the most used markers of cancer stem cells in several cancers, including colorectal cancer and breast cancer, is CD44. CD44 is a glycoprotein that traverses the cell membrane and binds to many ligands including hyaluronan resulting in activation of signaling cascades. Several reports have shown conflicting data on the expression of CD44 and that the expression depends on modes of investigations and subtypes of cancers. In addition, the correlation between CD44 expression and drug resistance, immune infi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 120 publications
1
27
0
Order By: Relevance
“…To go a step further, we explored the immunosuppressive role of CD44 in glioma. As reported, CD44 expression level is positively correlated with PD-L1, PD-1, IL10, and TGFB1 expression in some cancers (56,57). Thus, coexpression of CD44 and checkpoint family members were checked in glioma, and we found that CD44 expression positively correlates with the expression level of PD-L1 and PD-1 and correlates with the expression level of PDCD1LG2 (namely PD-L2) as well in the TCGA and CGGA glioma datasets (Supplementary Figure 10).…”
Section: Data Availability Statementmentioning
confidence: 64%
“…To go a step further, we explored the immunosuppressive role of CD44 in glioma. As reported, CD44 expression level is positively correlated with PD-L1, PD-1, IL10, and TGFB1 expression in some cancers (56,57). Thus, coexpression of CD44 and checkpoint family members were checked in glioma, and we found that CD44 expression positively correlates with the expression level of PD-L1 and PD-1 and correlates with the expression level of PDCD1LG2 (namely PD-L2) as well in the TCGA and CGGA glioma datasets (Supplementary Figure 10).…”
Section: Data Availability Statementmentioning
confidence: 64%
“…Compared with cells of a gastric cancer cell line, the expression of CD44 mRNA is significantly higher in gastric cancer stem cells (CSC-Gs) [ 15 , 16 ]. Abundant studies have demonstrated that CD44 serves as a marker for several tumour stem cells, including CSC-Gs [ 15 , 17 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few decades, our understanding of the genes, the pathways within which they function, and their role in oncogenesis have grown significantly and, along with this increased interest, concerted efforts to treat various cancer types [9][10][11][12][13][14] . Furthermore, various genetic aberrations have been identified in human cancers, and several of the proteins encoded by these genes are well-established drug targets, and others are promising drug targets 3,4,15,16 .…”
Section: Introductionmentioning
confidence: 99%